Sumberdaya Penghidupan Rumah Tangga Petani Padi Sawah Tadah Hujan (Studi Kasus di Kecamatan Kroya Kabupaten Indramayu) - Kusumo, Rani Andriani Budi; Mukti, Gema Wibawa; Charina, Anne (Universitas Galuh, 2024)
Farming households tend to develop multiple livelihood strategies to fulfil their needs, which can no longer be met by the agricultural sector. The livelihood strategy adopted by households relies on their livelihood assets or resources. This study aims to analyze the livelihood resources of wet-rice farming households in Kroya Subdistrict, Indramayu Regency. This research uses a qualitative design with a case study technique. The informants in this study were community leaders and village officials, while the participants were members of 50 rainfed wetland rice farming households. The data obtained were analyzed descriptively. The results showed that most farmer households also depend on the non-agricultural sector as a livelihood activity. The existence of social capital and easy access to financial resources are among the factors that attract many farming households to send one of their household members to work abroad as a livelihood activity option.